2011
DOI: 10.1128/jb.05555-11
|View full text |Cite
|
Sign up to set email alerts
|

Translocators YopB and YopD from Yersinia enterocolitica Form a Multimeric Integral Membrane Complex in Eukaryotic Cell Membranes

Abstract: The type III secretion systems are contact-activated secretion systems that allow bacteria to inject effector proteins across eukaryotic cell membranes. The secretion apparatus, called injectisome or needle complex, includes a needle that terminates with a tip structure. The injectisome exports its own distal components, like the needle subunit and the needle tip. Upon contact, it exports two hydrophobic proteins called translocators (YopB and YopD in Yersinia enterocolitica) and the effectors. The translocato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 35 publications
(41 reference statements)
1
54
0
Order By: Relevance
“…1). Therefore, the molecular mass obtained using this model system is in good agreement with the molecular mass roughly estimated for Yersinia translocons isolated from erythrocyte membranes using blue native gel electrophoresis (600 Ϯ 100 kDa) (42). Taken together, single molecule fluorescence and ensemble experiments suggest a model where the interaction of PopD with PopB, presumably a dimer formation, leads to the assembly of unique hetero-oligomeric structures with defined stoichiometry on lipid bilayers.…”
Section: Discussionsupporting
confidence: 79%
“…1). Therefore, the molecular mass obtained using this model system is in good agreement with the molecular mass roughly estimated for Yersinia translocons isolated from erythrocyte membranes using blue native gel electrophoresis (600 Ϯ 100 kDa) (42). Taken together, single molecule fluorescence and ensemble experiments suggest a model where the interaction of PopD with PopB, presumably a dimer formation, leads to the assembly of unique hetero-oligomeric structures with defined stoichiometry on lipid bilayers.…”
Section: Discussionsupporting
confidence: 79%
“…Translocon proteins form a hetero-oligomeric protein complex of presumably six to eight subunits with an internal diameter of approximately 1.2 to 3.5 nm (44,113,236,339,387,403,490,569). Recent crystal structure analysis of the translocon proteins IpaB from S. flexneri and SipB from Salmonella spp.…”
Section: Port Of Entry For Effector Proteins-the Translocon and The Tmentioning
confidence: 99%
“…For translocation of Yops to occur, Yersinia must insert two proteins, YopB and YopD, into the membranes of targeted cells (1,22). YopD, but not YopB, has been found in purified needle preparations from Yersinia enterocolitica; however, its location on or within these needles has not be visualized by EM (10,11).…”
mentioning
confidence: 99%
“…While it has been speculated that the YopD in these complexes is due to secreted but insoluble YopD which copurifies with needles (11,12), recent work has also shown that YopD copurifies with LcrVcapped needles (10). YopB and YopD form a hetero-oligomeric pore in mammalian plasma membranes, termed the translocon, and are critical for the formation of a pore through which effector proteins are thought to travel (1,22). Purified YopB and YopD can insert into lipid bilayers (23,24), most likely because of their hydrophobic nature.…”
mentioning
confidence: 99%